EFFECT OF PNEUMOPERITONEUM IN MODEL OF ABDOMINAL SEPSIS - Silva, Cybelle Dutra; Araújo Silva, Evelynne Mayara; Medeiros, Vítor Brasil; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
ABSTRACT Purpose: This study aims to examine the effects of CO2 pneumoperitoneum on the level of inflammation biomarkers in a model of abdominal sepsis in rats. Methods: Twelve Wistar rats were randomly assigned to two groups of 6 rats each. Under anesthesia, abdominal sepsis was induced by cecal ligation and puncture (CLP). Rats were observed for 24 hours. Group 1: sepsis; group 2: sepsis + pneumoperitoneum with CO2 for 30 min. Six hours after pneumoperitoneum deflation, blood samples were collected by cardiac puncture to measure (TNF?), interleukin-1? (IL-1?), interleukin-6 (IL-6), C-reactive protein (PCR) and procalcitonin (PCT). Statistical analysis using Student t test (p<0.05). Results: All animals survived. The rats with sepsis + pneumoperitoneum had levels of TNF?, IL-1? and IL-6 (542.4 ± 21pg / mL; 312.1 ± 12 pg / mL and 115.4 ± 11 pg / mL (respectively ), significantly lower than in the sepsis group (p = 0.01). Serum cytokine levels in the sepsis group were TNF? = 733.2 ± 24pg / mL; IL-1? = 432.1 ± 15 pg / mL and IL-6 = 232.3 ± 16 pg / mL. Serum levels of PCT and CRP were significantly lower in the sepsis + pneumoperitoneum group than in the sepsis group. (p=0.01). Conclusion: In conclusion, pneumoperitoneum CO2 attenuates the biomarkers of the acute phase inflammatory response associated with perioperative sepsis by PLC.